“Qual o valor da entrega?”: experiências de jovens trabalhadores e trabalhadoras em plataformas digitais de delivery - Oliveira, Caíque Diogo de (2024)
While young men and women faced the post-2013 economic crisis and the Covid-19 pandemic as adversities, delivery app platforms took advantage of the period of flexibility in labor legislation, social distancing and the closure of shopping centers to expand their businesses. . In the case of delivery cyclists, it is known that they are mostly young, men, black and residents of the city's outskirts. Taking the relationships between youth, education and work as a starting point, this study intends to analyze the experiences in “bike-delivery” work via apps in the city of São Paulo. To meet this objective, it is based on Thompson's notion of experience (1981, 1987), giving centrality to daily work, the trajectories and meanings attributed to work. These experiences are also investigated based on interpretations based on intersectionality (ANDERSEN; HILL COLLINS, 2007; HILL COLLINS; BILGE 2021; HILL COLLINS, 2022; CARVALHO, 2020) and its variable geometries (HIRATA, 2020) that are articulated from age, gender, race and class. The research, of a qualitative nature, mainly used interviews carried out remotely, between the years 2021 and 2023, in addition to field observations on the streets and on social networks. 12 young cyclist delivery drivers were interviewed, 9 who identified themselves as men, 3 women. If in several countries in the global north app delivery people are, in general, immigrants or poor workers who do “odd jobs” to support themselves, in Brazil, bike delivery work involves a segment of the population that has historically had access to a job with rights denied, seeking different ways to “make a living”. This thesis argues that the youth condition structures the work experience on platforms in the form of bike deliveries, indicating permanence and transformations in the world of work. Among the permanences, the results point to the continuity of a pattern in Brazilian capitalism marked by the exploitation of the vital moratorium of the young, male and black body working on the city streets, based on a precarious and risky activity. Cycle delivery drivers criticized the applications and low pay; however, at the same time, they criticized the configuration of formal employment today. Regarding trajectories, the data indicate that permanence and provisionality have gender and race. Among young women, there is greater temporariness, as well as for white boys. On the other hand, for black men, there is a greater permanence in the activity, whether as cyclists or joining the motorcycle delivery sector. In a scenario where safe and legally protected work is not available to everyone, digital delivery platforms appear as an accessible means for young people from the lower classes to put into practice individual strategies to earn a living.